(untitled) (Eventum: A Journal of Medieval Arts & Rituals, 2023)
This article investigates the intriguing pilgrim cult of a Cypriot saint, John Lampadistes, during the Middle Ages. It considers first the development of the saint’s cult, and his shrine in the Marathasa Valley as a place of pilgrimage. The complex architectural space and the physical presence of the tomb, relics, and vita-icons of St John Lampadistes were the focal point of the pilgrims’ unique religious experiences. Subsequently, the article attempts to reconstruct the routes taken by pilgrims and to determine who might have promoted the pilgrimage to the saint’s shrine. Finally, the spread of the saint’s cult around the island of Cyprus is examined.